Dear zoo - Campbell, Rod, 1945- (New York : Little Simon, 2019)
Each animal arriving from the zoo as a possible pet fails to suit its prospective owner, until just the right one is found. Movable flaps reveal the contents of each package.
Keywords: Lift-the-flap books -- Specimens; Zoo animals -- Juvenile fiction; Lift-the-flap books; Zoo animals; Fiction; Juvenile works; Specimens